Komunikasi Ritual pada Budaya Bertani Atoni Pah Meto di Timor-Nusa Tenggara Timur - Yermia Djefri Manafe (Asosiasi Pendidikan Tinggi Ilmu Komunikasi (ASPIKOM), 2011)
The ritual is one way of communicating. All forms of ritual is communicative. The ritual is always a symbolic behavior in social situations. Because of this ritual is always a way to communicate something. Communication rituals can be understood as meaning the message of a group of people against religious activity and belief system that was followed. The ritual is performed Atoni Pah Meto not independent of trust they hold, in the process always happen meaning of certain symbols that signify the process of ritual communication. This symbol has a meaning known only to those who perform the ritual.